A high performance phenyl-free LED photoinitiator for cationic or hybrid photopolymerization and its application in LED cationic 3D printing. Issue 16 (1st April 2020) - Tang, Liqun; Nie, Jun; Zhu, Xiaoqun
Abstract : In this work, a high performance LED photoinitiator, 1, 3-bis(1-methyl-1 H -pyrrol-2-yl)prop-2-en-1-one (BMO), without a benzene ring was synthesized through a one-step aldehyde–ketone condensation reaction. Abstract : In this work, a high performance LED photoinitiator, 1, 3-bis(1-methyl-1 H -pyrrol-2-yl)prop-2-en-1-one (BMO), without a benzene ring was synthesized through a one-step aldehyde–ketone condensation reaction. BMO has a broad absorption range and a high molar extinction coefficient from 365 to 425 nm. Interestedly, BMO can be used not only as a type II free radical photoinitiator for which the hydrogen donor can be supplied by itself or other tertiary amines, but also as a long wavelength sensitizer to sensitize diphenyliodonium photoinitiators (Iod) under a 365 nm to 425 nm LED lamp. BMO/Iod can initiate cationic and free radical photopolymerization. It also can initiate the hybrid photopolymerization efficiently. As a sensitizer to Iod, its activity in initiating cationic photopolymerization is not less than that of 2-isopropylthioxanthone (ITX). In particular, it remains highly active at a low light intensity under a LED lamp. This is very significant to the cationic photopolymerization as well as the photocuring 3D printing technique.